Obtenção da curva de retenção da água no solo pela câmara de compressão triaxial e pelo papel filtro - Lucas, Juliana Fenner Ruas (2010)
The soil water content is related to the soil matrix ability to retain the water, characterized by the water matric potential. Moisture and matric potential are factors functionally interrelated and represented by the soil-water retention curve. This relationship allows inferring moisture from the matric potential measurement and vice versa, as well as deducing several soil and water in soil properties. The traditional method for determining the retention curve employs the Richards pressure plate apparatus. For practical reasons, the search for alternatives to the Richards apparatus that are financially more accessible and faster is needed. In this regard, this study aimed at evaluating the use of two devices: the triaxial compression chamber and the filter paper. Therefore, soil was initially collected and physical-chemically characterized. Undisturbed soil samples were prepared and tested in the Richards chamber, using pressures of 0, 10, 30, 60, 100, 300, 500, 1,000 and 1,500 kPa. In the triaxial compression chamber test, soil samples were submited to pressures of 0, 10, 30, 60, 100, 300, 500 and 1,000 kPa, and for each pressure, it was measured the volume of drained water and calculated the sample moisture at that pressure. In the filter paper test, it was measured the water matric potential in samples for which moisture levels were established using an appropriated calibration curve. The three tests were repeated five times, resulting in points of pressure versus moisture that were adjusted by the RETC program, using to the model of van Genuchten. It was performed a comparative analysis of the triaxial chamber and the filter paper estimated soil moisture values with the adjusted retention curve obtained by the Richards apparatus. This comparison allowed to verify the applicability of the filter paper method for determining the water retention curve in agricultural soils and the inadequacy of triaxial compression chamber for this purpose.